Analisis Perbandingan Unjuk Kerja Motor Bensin Dengan Penambahan Groundstrap dengan Material Tembaga Dan Perak Pada Kabel Koil Busi - Wijaya, Hardian Putra; Dantes, Kadek Rihendra; Wiratmaja, I Gede (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2021)
This research aimed to (1) Determining the differences in power and torque to use of a coil standard, a copper, and silver wire ground strap variation coils. (2) Determining the color characteristics of the sparks' size generated from the use of standard coils, variation coils of copper, and silver ground strap. This research used an experimental method. The data analysis technique used descriptive analysis, namely, observing and recording the test results and then concluding in tables and graphs. The test results show that an increase in power, and torque is generated in this test. The highest results were obtained using a silver ground strap variation coil with a power of 11.3 hp and torque of 12.05 Nm. In this case, the percentages are 7.6% and 7.8% from the lowest results of the standard coil. There are different colors, sizes, and characters obtained in the test of sparks. The dark blue-purplish sparks color is obtained from the silver wire ground strap variation coil, which can increase motor performance in a motorcycle. These results suggest that the ground strap on the spark plug coil wire can provide an increment in engine performance.